Is Haplothrips clarisetis Priesner (Thysanoptera: Tubulifera) an Economic Threat to Table Grapes in the Lower Orange River Production Region of South Africa? - Allsopp, Elleunorah; Stiller, Michael (South African Journal of Enology and Viticulture, 2022)
Table grape producers and consultants in the Lower Orange River region, Northern Cape province, have been reporting conspicuous, fairly large, black thrips on new growth and inflorescences early in the growing season in recent years. These thrips were identified as Haplothrips clarisetis Priesner and H. nigricornis Bagnall, both indigenous species widely distributed in South Africa and Africa. The aim of this investigation was to determine if H. clarisetis causes any damage to table grapes and if it poses an economic threat to the industry in the Northern Cape province. Inspections were conducted over two seasons during flowering and fruit set, prior to and after harvest in four vineyards near Augrabies (28.7630 S, 20.5668 E) and four in the Blouputs Valley (28.4631 S, 20.0789 E) where Haplothrips had previously been reported. Developing inflorescences, bunches, leaves and shoot tips were inspected for the presence of Haplothrips and for any signs of feeding damage. Very few thrips were found and no signs of feeding were observed. Adult H. clarisetis were collected from flowering grape bunches and from flowers of Osteospermum microcarpum (Asteraceae) and Mesembryanthemum crystallinum (Aizoaceae) growing wild adjacent to the vineyards and confined on grapevine flowering bunches, leaves and a single shoot tip. Daily inspections showed no signs of feeding damage on the shoot tip, leaves or inflorescences and thrips did not survive for more than three days on average. We therefore conclude that H. clarisetis does not pose an economic threat to table grapes in the Lower Orange River region.